2009
DOI: 10.1159/000246579
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Keratoplasty without Descemet’s Membrane Stripping: Histologic and Ultrastructural Findings

Abstract: Aim: To report histologic and ultrastructural findings of endothelial keratoplasty (EK) performed without Descemet’s membrane stripping. Methods: Clinical techniques, histology, and transmission electron microscopy. Results: A 55-year-old woman was referred to us, after 2 unsuccessful penetrating keratoplasties (PKs), for pseudophakic bullous keratopathy. An 8.0-mm EK without Descemet’s membrane stripping was performed, and clarity was restored to the failed penetrating regraft. A year later, the lamellar graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, isolated cases published in the literature support the feasibility of EK without stripping the DM in patients with failed grafts 1 2. Based on our observation of favourable outcomes after EK without stripping the DM in patients with no clinical evidence of DM pathology, we hypothesise that Descemet's stripping may be an avoidable intraoperative step in EK for the indications where it is expected to be normal and optically clear.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…However, isolated cases published in the literature support the feasibility of EK without stripping the DM in patients with failed grafts 1 2. Based on our observation of favourable outcomes after EK without stripping the DM in patients with no clinical evidence of DM pathology, we hypothesise that Descemet's stripping may be an avoidable intraoperative step in EK for the indications where it is expected to be normal and optically clear.…”
mentioning
confidence: 72%
“…Several observations provide evidence towards this hypothesis 1. Histological study of failed Descemet's stripping endothelial keratoplasty buttons has shown that the presence of residual DM was not associated with any alteration in cellularity or inflammation 2 3…”
Section: Discussionmentioning
confidence: 99%
“…There are various intra-operative difficulties in performing EK in CHED patients which include poor visibility due to very severe corneal oedema in these cases 13 and strong adherence of the Descemet membrane to the underlying stroma which could result in DM retention and graft failure. 21 Stripping of DM is much easier in decompensated corneas due to other causes such as Fuch’s endothelial dystrophy (FECD) in contrast to the CHED eyes. 22 This might result in residual DM remnants which would hinder the graft apposition.…”
Section: Discussionmentioning
confidence: 99%
“…Performing EK in CHED patients is associated with various intraoperative difficulties: poor visibility due to severe corneal edema and strong adherence of the DM to the underlying stroma, which may result in DM retention/tags, leading to graft detachment and failure. [ 15 16 ] DM scoring is found to be much simpler in decompensated corneas such as Fuchs’ endothelial dystrophy in contrast to the CHED eyes. [ 17 ]…”
mentioning
confidence: 99%